2012
DOI: 10.1182/blood-2011-04-347476
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 interacts with AML1-ETO to promote its transcriptional activation and progenitor cell proliferative potential

Abstract: Fusion protein AML1-ETO, resulting from t(8;21) translocation, is highly related to leukemia development. It has been reported that full-length AML1-ETO blocks AML1 function and requires additional mutagenic events to promote leukemia. We have previously shown that the expression of AE9a, a splice isoform of AML1-ETO, can rapidly cause leukemia in mice. To understand how AML1-ETO is involved in leukemia development, we took advantage of our AE9a leukemia model and sought to identify its interacting proteins fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 52 publications
4
111
0
Order By: Relevance
“…KLF4 increased expression of E2F2, which encodes a transcriptional regulator involved in hematopoietic stem cell self-renewal and differentiation (45). Conversely, KLF4 decreased expression of the oncogenes PRMT1 and BTK, which have known roles in leukemia (46,47). These changes were confirmed by RT-qPCR and Western blot analysis ( Fig.…”
Section: Klf4 Expression Is Decreased In Primary Patient Aml Casessupporting
confidence: 65%
See 1 more Smart Citation
“…KLF4 increased expression of E2F2, which encodes a transcriptional regulator involved in hematopoietic stem cell self-renewal and differentiation (45). Conversely, KLF4 decreased expression of the oncogenes PRMT1 and BTK, which have known roles in leukemia (46,47). These changes were confirmed by RT-qPCR and Western blot analysis ( Fig.…”
Section: Klf4 Expression Is Decreased In Primary Patient Aml Casessupporting
confidence: 65%
“…As a transcriptional regulator, E2F2 regulates the balance of stem cell self-renewal and differentiation of erythrocytes (45), and it may also play a role in myeloid differentiation. KLF4 decreased expression of the oncogene PRMT1, whose knockdown reduces the growth and survival of leukemic cells (46). Lastly, KLF4 expression decreased BTK expression.…”
Section: Discussionmentioning
confidence: 99%
“…11 On the other hand, AML1/ETO can also recruit coactivators (such as p300 and PRMT1) to activate genes, especially those involved in stem cell self-renewal, such as ID1, CDKN1A, and EGR1. 12,13 In addition to dynamic interactions with various regulatory (co)factors, a recent study has reported that AML1/ETO resides in and functions through a stable multiprotein complex that at least contains HEB, LYL1, LMO2, and CBFb, 14 providing another layer of regulatory complexity for AML1/ETO in regulating its target genes.…”
Section: Introductionmentioning
confidence: 99%
“…AML1/ETO has recently been reported to interact with p300 or PRMT1: both are essential for AML1/ETO-mediated gene activation and leukemogenesis. 12,13 Given the known modulatory effects of PRMT1 and p300 on AP-1-mediated regulation, 54,55 we assume that AP-1, p300, and PRMT1 may function together in the AML1/ETO-AML1 complex.…”
mentioning
confidence: 99%
“…AE9a lacks the conserved ETO domains NHR3/4, whose interaction with corepressor proteins such as N-CoR/SMRT and HDACs is important for transcriptional repression (17)(18)(19)(20). Despite maintaining some corepressor interaction, AE9a has greatly diminished N-CoR and SMRT interaction and is a much less potent transcriptional repressor than full-length AE (17,(19)(20)(21)(22). The AML1-ETOtr mutant showed altered regulation of cell cycle proteins, thereby providing a proliferative advantage in K562 cells relative to AE (15).…”
mentioning
confidence: 99%